2017
DOI: 10.1136/heartjnl-2017-311598
|View full text |Cite
|
Sign up to set email alerts
|

Developing a shared decision support framework for aortic root surgery in Marfan syndrome

Abstract: ObjectiveThe study is an early phase of development of a decision support framework for people with Marfan syndrome who are anticipating prophylactic aortic root surgery. Implications of the timing and the nature of the operation chosen were previously elicited in focus groups. In this step, we explored the range of relative values placed by individuals on the implications of decisions made about surgery.MethodsFollowing the principles of the Ottawa Decision Support Framework, eight questions in the general fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…27 Treasure et al address the concerns of preserving QoL for MFS patients and its role in treatment decisions. 28 Lastly, Benninhoven et al found that rehabilitation programs for individuals with MFS can make a significant impact in their QoL. 25 Children and Adolescents…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Treasure et al address the concerns of preserving QoL for MFS patients and its role in treatment decisions. 28 Lastly, Benninhoven et al found that rehabilitation programs for individuals with MFS can make a significant impact in their QoL. 25 Children and Adolescents…”
Section: Resultsmentioning
confidence: 99%
“…Of the literature reviewed and categorized into the adults theme, 23 articles evaluated either QoL directly or factors that impact QoL such as employment in adults. 9,11,12,14,[19][20][21][22][23][24][25]27,28,[30][31][32]40,49,[53][54][55][56][57] Velvin et al and Velvin et al are two reviews that focus on QoL. Having a diagnosis of MFS alone will likely impact QoL.…”
Section: Factors That Impact Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Their ideas and preferences may play an important role in the method and timing of elective aortic root replacement, as addressed by Tom Treasure and colleagues6 (Developing a shared decision support framework for aortic root surgery in Marfan syndrome) in their  Heart  paper. Treasure and colleagues investigated HTAD patient and doctor preferences about the type and timing of aortic root surgery in an international cohort.…”
Section: Physicians and Patientsmentioning
confidence: 99%
“…Treasure and colleagues1 present the first steps toward a decision support framework for timing of aortic root surgery in adults with Marfan syndrome. Patients, family members and providers were asked to rank the importance of several factors including timing of surgery (postpone vs get it over with); avoiding anticoagulation (particularly if pregnancy is being considered); avoiding other medications, hospital tests or noise from the prosthetic valve; and having an active lifestyle.…”
mentioning
confidence: 99%